Reaching the last mile: best practices in leveraging the power of ICTs to communicate climate services to farmers at scale - Davis, Alicia; Tall, Arame; Dileepkumar, Guntuku (2014)
This report reviews key ICTs for Development (ICT4D) Programs, Innovations and Information Exchange Platforms which are experimented within South Asia to explore the use and scale-ability of these innovative approaches to other parts of Africa and the developing world. Learning from the pioneering experiences of pilot projects across India and Africa in ICT development, we assess the potential ICTs offer to not only communicate climate information and related advisory services but also to build capacity and increase the resilience of rural smallholders. It is our hope that such South-South learning can pave the way for improved cross-regional experience sharing to tackle common challenges in reaching ‘the last mile’ with salient rural extension services, including climate information services.